2019
DOI: 10.1155/2019/3752645
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Outcome of Esophageal Button Battery Ingestion in Children: An 8-Year Retrospective Case Series

Abstract: Objective To present the clinical profile and outcomes of esophageal button battery ingestion cases treated at our institution over an 8-year period. Methods A total of 17 children who presented after ingesting a button battery and were treated at a tertiary care clinic over an 8-year period were included in this retrospective case series study. Data on patient demographics and esophageal location of the battery, time from ingestion to admission, symptoms, grade of mucosal injury, size of the battery, manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…The most frequent symptom in both EB and GB was vomiting (50%), followed by sialorrhea (30%), fever (20%), and refusal to eat and prostration (15%). These results are similar to what is reported in literature ( 5 , 13 , 19 , 20 ) and reflect the high number of cases in whom a later than recommended removal was performed, showing symptoms of potential complications. In patients with GB, two had esophageal lesions that could explain these symptoms (one patient with abdominal pain had a Grade IIa esophageal and gastric injury, and another one with vomiting and sialorrhea also had a Grade IIa esophageal lesion).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The most frequent symptom in both EB and GB was vomiting (50%), followed by sialorrhea (30%), fever (20%), and refusal to eat and prostration (15%). These results are similar to what is reported in literature ( 5 , 13 , 19 , 20 ) and reflect the high number of cases in whom a later than recommended removal was performed, showing symptoms of potential complications. In patients with GB, two had esophageal lesions that could explain these symptoms (one patient with abdominal pain had a Grade IIa esophageal and gastric injury, and another one with vomiting and sialorrhea also had a Grade IIa esophageal lesion).…”
Section: Discussionsupporting
confidence: 91%
“…Battery ingestions are more frequent in small children, and associated complications are also more prevalent in children <5 years ( 7 , 9 ). In our study, the median age was 26 months, similar to what is reported in other series ( 5 , 6 , 18 ), and 75% of children were younger than 5 years. Despite perforation in our sample was more frequent in younger patients, this relationship was not statistically significant either.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations